2020
DOI: 10.2147/jpr.s248424
|View full text |Cite
|
Sign up to set email alerts
|

<p>Sex and Gender are Not the Same: Why Identity Is Important for People Living with HIV and Chronic Pain</p>

Abstract: Background: Sex differences in pain sensitivity have been well documented, such that women often report greater sensitivity than men. However, clinical reports highlighting sex differences often equate gender and sex. This is a particularly critical oversight for those whose gender identity is different than their genetic sex. Methods: This preliminary study sets to analyze differences in pain responses between cisgender and transgender individuals living with HIV and chronic pain. A total of 51 African-Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 62 publications
(72 reference statements)
0
20
1
2
Order By: Relevance
“…Although the findings presented in the current review may have been drawn from cisgender samples, future research should test associations between pain and substance use among transgender and gender minority populations. 134 , 135 Additionally, despite documented racial/ethnic disparities in the prevalence, treatment, and outcomes of pain-related conditions, 136 , 137 this review identified only one study that examined the current constructs of interest among racial/ethnic minorities. 97 A recent review of racial and ethnic disparities in chronic pain treatment found that Black patients maintained on long-term opioid medication were more closely monitored for misuse, despite higher rates of opioid misuse and opioid-related overdose deaths observed among Whites.…”
Section: Discussionmentioning
confidence: 99%
“…Although the findings presented in the current review may have been drawn from cisgender samples, future research should test associations between pain and substance use among transgender and gender minority populations. 134 , 135 Additionally, despite documented racial/ethnic disparities in the prevalence, treatment, and outcomes of pain-related conditions, 136 , 137 this review identified only one study that examined the current constructs of interest among racial/ethnic minorities. 97 A recent review of racial and ethnic disparities in chronic pain treatment found that Black patients maintained on long-term opioid medication were more closely monitored for misuse, despite higher rates of opioid misuse and opioid-related overdose deaths observed among Whites.…”
Section: Discussionmentioning
confidence: 99%
“…The patient is a transgender male who visited multiple emergency departments and had a delayed diagnosis possibly due to several reasons. These reasons may include the patient leaving AMA before further evaluation could be performed; the perception of the patient’s pain/clinical picture not matching the “expected” presentation of ovarian torsion; the patient’s unwillingness to endorse true pain level for fear of being gendered [ 9 , 10 ]; and, lastly, the inexperience with this condition in such populations. Cases like this can perhaps be seen as a challenge to all generalizations, as every patient is unique.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, gender is now recognized as existing along a spectrum, yet virtually all pain research continues to operationalize gender as binary, and gender identity as a determinant of health has seldom been examined 56 (but see two recent studies examining pain among transgender individuals). 68,96 Between-group analysis risks obscuring the diversity that exists within most research samples, and meaningful information is lost that could help identify accurate targets for interventions.…”
Section: Underrepresented Groupmentioning
confidence: 99%